Predictive value of cough peak flow for successful extubation in mechanically ventilated patients after craniotomy: a single-centre prospective diagnostic study - Guang Zhi Shi; Linlin Zhang; Jian-Xin Zhou; Ming Xu; Yan-Lin Yang; Jianfang Zhou; Hong-Liang Li; Xu-Ying Luo; Guang-Qiang Chen (BMJ Open)
Objectives The purpose of this study was to evaluate the predictive value of the cough peak flow (CPF) for successful extubation in postcraniotomy critically ill patients.Design This was a single-centre prospective diagnostic study.Setting The study was conducted in three intensive care units (ICUs) of a teaching hospital.Participants Postcraniotomy patients who were 18 years or older, stayed in ICU for more than 24 hours and underwent mechanical ventilation for more than 24 hours were eligible for the study. Patients were excluded if one of the following was present: no extubation attempt during the ICU stay; underwent tracheostomy without extubation attempt; pregnant or lactating women; enrolled in other clinical trials; declined to participate in the study. A total of 4879 patients were screened and 1037 were eligible for the study, among whom 785 were included in the study.Outcome measures CPF, including involuntary (CPF-invol) and voluntary CPF (CPF-vol), were measured before extubation. The area under the receiver operating characteristic curve (AUC) was calculated to explore the diagnostic accuracy of CPF in predicting successful extubation.Results There were 641 successful extubation cases (81.7%). The AUC of CPF-invol for predicting successful extubation was 0.810 (95% CI 0.766 to 0.854), with a cut-off value of 63.2 L/min, a sensitivity of 87.4% and a specificity of 66.7%. For conscious patients, the AUC of CPF-invol for the prediction of successful extubation was 0.849 (95% CI 0.794 to 0.904), with a cut-off value of 63.2 L/min and the AUC of CPF-vol was 0.756 (95% CI 0.696 to 0.817), with a cut-off value of 68.2 L/min.Conclusions The CPF was much higher in patients with successful extubation than that in patients with failed extubation. CPF might be valuable for the prediction of extubation outcomes in postcraniotomy critically ill patients. Multicentre studies could be carried out to further validate the results of this study.Trial registration number NCT04000997.